2011
DOI: 10.1108/00907321111161449
|View full text |Cite
|
Sign up to set email alerts
|

Text reference service: delivery, characteristics, and best practices

Lili Luo

Abstract: Purpose -The purpose of this paper is to present a detailed depiction of the text reference environment and its affordance, and suggest strategies to help librarians adhere to the Reference and User Services Association (RUSA) behavioral guidelines in text reference service. Design/methodology/approach -The author reviews the current text reference literature as well as conducts qualitative and quantitative analysis of reference services provided by My Info Quest, the USA's first collaborative text reference s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Because of the relatively nascent nature of text reference service, there has not been much literature on its evaluation from the user perspective. Most of the text reference literature focus on how the service is established and managed, what kinds of questions are answered, and how librarians think of it (Giles and Grey- Smith, 2005;Hill et al, 2007;Herman, 2007;Profit, 2008;Kohl and Keating, 2009;Weimer, 2010;Pearce, 2010;Jensen, 2010;Stahr, 2009Stahr, , 2011Cole and Krkoska, 2011;Luo and Bell, 2010;Avery et al, 2010;Weak, 2011, 2012;Luo, 2011Luo, , 2012Brooks and Zubarev, 2012;Vecchione and Ruppel, 2012). A few studies, when reporting individual libraries' experience of implementing text reference service, briefly discussed users' view of the service.…”
Section: User-oriented Reference Evaluation Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the relatively nascent nature of text reference service, there has not been much literature on its evaluation from the user perspective. Most of the text reference literature focus on how the service is established and managed, what kinds of questions are answered, and how librarians think of it (Giles and Grey- Smith, 2005;Hill et al, 2007;Herman, 2007;Profit, 2008;Kohl and Keating, 2009;Weimer, 2010;Pearce, 2010;Jensen, 2010;Stahr, 2009Stahr, , 2011Cole and Krkoska, 2011;Luo and Bell, 2010;Avery et al, 2010;Weak, 2011, 2012;Luo, 2011Luo, , 2012Brooks and Zubarev, 2012;Vecchione and Ruppel, 2012). A few studies, when reporting individual libraries' experience of implementing text reference service, briefly discussed users' view of the service.…”
Section: User-oriented Reference Evaluation Researchmentioning
confidence: 99%
“…She noted that "a few students did indicate that cost might be a barrier to their use of text reference service, adding comments such as 'most important factor is cost; it costs me 10 cents to send a text message'". Luo (2011) surveyed a small sample of 19 users of a collaborative text reference service and found that the majority of the respondents were regular texters with unlimited texting on their mobile service plan. They mostly elected to employ the service due to urgent information needs and they appreciated the convenience and speed of the service.…”
Section: User-oriented Reference Evaluation Researchmentioning
confidence: 99%
“…Luo (2011) discovered that participants at San Jose State University used SMS because they needed information immediately (55.6 per cent), wanted to see how the service worked (38.9 per cent), did not have Internet access (33.3 per cent) and needed help from…”
Section: Phone/sms Reference Servicementioning
confidence: 99%
“…• 93.5 per cent used their handheld mobile device to send or receive text messages; and • more BSU students owned a cell phone than use popular social networking sites, including Twitter and Facebook (EDUCAUSE Center for Applied Research, 2010). Luo (2011) discovered that participants at San Jose State University used SMS because they needed information immediately (55.6 per cent), wanted to see how the service worked (38.9 per cent), did not have Internet access (33.3 per cent) and needed help from…”
Section: Phone/sms Reference Servicementioning
confidence: 99%
“…As evidenced by the BSU ECAR survey results, the authors have found that SMS usage has increased since the time it was introduced in 2010. Luo (2011) reported that San Jose State University survey participants used SMS because they needed information immediately (55.6 percent), wanted to see how the service worked (38.9 percent), did not have internet access (33.3 percent), and needed help from a librarian (16.7 percent). In addition, 88.9 percent of the participants said RSR 40,3 they would be willing to use the service again (Luo, 2011).…”
Section: Sms Referencementioning
confidence: 99%